(untitled) (Research, Society and Development, 2020)
The purpose of this article is to critically present to the Portuguese-language reader the series of documents on digital competences called DigComp, prepared by the European Commission’s Joint Research Center (JRC), in addition to other related reports. The methodology included research on the Internet, a systematic literature review and critical reading of documents. The results indicated that these documents are based on a series of Communicatios of the European Commision and Recommendations of the European Parliament, published between 2006-2018, which point to the necessary competences for lifelong learning, amongst which digital competences, besides presenting the commitments made by the European Union on this front. Different frameworks were then developed: DigComp 1.0, DigComp 2.0 and DigComp 2.1, aimed at citizens, in addition to DigComp into action, with examples and practical cases; DigCompEdu, DigCompOrg and OpenEdu, focused on education; and DigCompConsumers and EntreComp, focused on business, in addition to EntreComp into action, with examples and practical cases. These documents are presented, compared, and discussed. Studies of general trends in these areas were also identified, which are mentioned but not discussed in this article, on topics such as: MOOCs, makerspaces, learning analytics, computational thinking, blockchain and policies for the integration and innovative use of digital technologies in education. The article concludes that these frameworks are important milestones for understanding and developing digital competences, however, there is not a wealth and series of similar documents developed in Brazil.